2002
DOI: 10.1002/cne.10490
|View full text |Cite
|
Sign up to set email alerts
|

Olivocochlear innervation in the mouse: Immunocytochemical maps, crossed versus uncrossed contributions, and transmitter colocalization

Abstract: To further understand the roles and origins of gamma-aminobutyric acid (GABA) and calcitonin gene-related peptide (CGRP) in the efferent innervation of the cochlea, we first produced in the mouse an immunocytochemical map of the efferent terminals that contain acetylcholine (ACh), CGRP, and GABA. Olivocochlear (OC) terminals in inner and outer hair cell (IHC and OHC) regions were analyzed quantitatively along the cochlear spiral via light-microscopic observation of cochlear wholemounts immunostained with antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
176
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(190 citation statements)
references
References 49 publications
13
176
1
Order By: Relevance
“…In this study, we observed the morphological degeneration of stereocilia in the apical turn as well as in the basal turn, but not in the mid-turn, in C57mice at P6mo, which supports our hypothesis of a close relationship between MOC efferent function and OHC degeneration. It was previously reported that MOC innervation is densest at the mid-turn of the mouse cochlea, roughly at the 10-kHz region in the OHC areas, and that MOC innervation decreases both apically and basally (Maison et al, 2003). The function of the MOC efferent system is to protect the ear from acoustic injury.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we observed the morphological degeneration of stereocilia in the apical turn as well as in the basal turn, but not in the mid-turn, in C57mice at P6mo, which supports our hypothesis of a close relationship between MOC efferent function and OHC degeneration. It was previously reported that MOC innervation is densest at the mid-turn of the mouse cochlea, roughly at the 10-kHz region in the OHC areas, and that MOC innervation decreases both apically and basally (Maison et al, 2003). The function of the MOC efferent system is to protect the ear from acoustic injury.…”
Section: Discussionmentioning
confidence: 98%
“…Although cochlear de-efferentation can dramatically increase noise-induced permanent threshold shifts (Kujawa and Liberman, 1997), the sound pressures required to produce such shifts are high, e.g., 105-110 dB SPL for 2 h (Rajan and Johnstone, 1989;Robertson and Anderson, 1994;Reiter and Liberman, 1995;Maison et al, 2002). Thus, OC-mediated protection may be an epiphenomenon (Christopher Kirk and Smith, 2003): i.e., important in industrialized society where intense noise is rampant, but unlikely to represent the selective pressure explaining the evolution of this feedback system.…”
Section: Discussionmentioning
confidence: 99%
“…2A). Based on published reports of the innervation patterns in mouse (Brown, 1993;Maison et al, 2003), a midline cut should remove approximately two-thirds of the MOC projections to both ears. If the cut is off midline, it will begin to impinge on some of the axons of ipsilaterally projecting MOC and LOC cells.…”
Section: Assessing Cochlear De-efferentation Via Cholinergic Immunostmentioning
confidence: 99%
“…Medial olivocochlear (MOC) neurons have cell bodies in the medial part of the superior olivary complex and project to outer hair cells. Lateral olivocochlear (LOC) neurons have cell bodies in or around the lateral superior olive and project to afferent fibers near inner hair cells (Warr and Guinan, 1979;Liberman, 1980;Liberman and Brown, 1986;Brown, 1987;Vetter and Mugnaini, 1992;Maison et al, 2003). Cholinergic MOC endings in the cochlea exert their effects by means of a nicotinic receptor (Vetter et al, 1999;Elgoyhen et al, 2001Elgoyhen et al, , 2003 that influences outer hair cell function and alters cochlear responses (Wiederhold and Kiang, 1970;Mountain, 1980;Siegel and Kim, 1982;Brown and Nuttall, 1984).…”
Section: Introductionmentioning
confidence: 99%